Janiceps Perosomus Elumbis: A Rare Fetal Monstrosity in Holstein Friesian Cattle - Gulia, N.; Bisla, A.; Honparkhe, M.; Singh, B. (The Indian Journal of Animal Reproduction, 2021)
The present clinical article reports a rare case of Janiceps Perosomus elumbis fetal monster in a Holstein Friesian (HF) cross bred cattle and its successful per-vaginal delivery using partial fetotomy. A HF crossbred cattle was presented with history of completed gestation period with rupture of water bag 6 h ago and straining with failure of delivery of fetus per-vaginum. The animal was examined at field level and both forelimbs were pulled by the local paravet with retention of head inside the birth canal. Per-vaginal examination revealed fetus in anterior longitudinal presentation, dorso-sacral position with both forelimbs extended in birth canal and two heads. The fetotomy was done for decapitation of both the heads. Then, the fetus was delivered per vaginal by traction. The fetal monster was enumerated as “Janiceps Perosomus elumbis” as the two heads were facing opposite to each other with absence of vertebrae after thoracic region.